A Study of Coping Mechanisms among Women Subjected to Intimate Partner Violence in the Urban Context of Faisalabad - Fouzia Mumtaz; Muhammad Usman; *Dr. Madiha Naz; Dr. Sana Ejaz (Review Journal of Social Psychology & Social Works, 2025)
Intimate partner violence (IPV), that remains to be a terrible and widespread issue that damages women mentally as well as physically and encourages violent practices, affects many women worldwide. In Pakistan's urban areas of District Faisalabad, assault by intimate partners poses a serious risk to women's safety and welfare in close relationships. The objective of this qualitative study is to explore the coping techniques that women in this urban context who were victims of violence in intimate relationships have used in order to deal with the trauma they have experienced. It is important to comprehend the coping strategies used by women in the face of IPV for a number of reasons. The metropolitan region of District Faisalabad is the site of this study. Purposive sampling is the sample technique employed in this investigation. Twenty-five women who had experienced domestic abuse were selected by the researcher, who carried out a qualitative investigation. Key informant interviews, focus groups, and in-person interviews are used to gather data. Women who had been in a close relationship for a year or more and were among between the ages of 18 and 40. This research outlines a variety of psychosocial elements linked to coping methods and feminine mistreatment in the city. This research outlines a variety of psychosocial elements linked to coping methods and feminine mistreatment in the city. Generally speaking, the accounts of women who have been exploited show that while violence is common for many reasons (economic, cultural, and societal), some women are skilled at it and are introverted. The stress and hardships that victims of violence face may be greatly reduced by using management strategies include setting priorities, keeping an optimistic outlook, asking for help from non-religious groups and official agencies, and talking to informal networks about problems. Victims of abuse can get rid of these problems by using these general ways to cope and ways that are specific to the social situation.